ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN BURUH DI KECAMATAN BONANG KABUPATEN DEMAK - Wijayanto, Dian Daru; Prajanti, Sucihatiningsih Dian Wisika (Journal of Economics and Business, 2019)
This study was purposed to analyse fishermen welfare level in Kecamatan Bonang Kabupaten Demak viewed in terms of income and expense, environmental condition and residence facility, and efforts taken to solve fishermen society obstacles in order to improve their prosperity. This was included in qualitative study. Data was collected through observation, questionnaire, and interview techniques and analysed using interactive model qualitative approach. According to study result, it was found that more than a half of fishermen quantity in Kecamatan Bonang was classified as Unprosperous Family. Low level of fishermen welfare was caused by working dependence of natural condition and state of mind and lifestyle that lack of improvement wish. Some efforts taken to improve people welfare in Kecamatan Bonang were as follows: distributing Bantuan Langsung Mandiri (BLM) and fishing equipment aid, building fishermen group cooperation with banking institution, improving fishermen resource quality, improving fishermen participation to develop fishery business, improving fishery and marine infrastructure, and maintaining marine environment.